Organic geochemistry of sediments at DSDP Legs 56-57 Holes - Jürgen Rullkötter; C Cornford; Pierre Flekken; Dietrich Hugo Welte (PANGAEA, 1980)
The quantity, type, and maturity of the organic matter of Quaternary and Tertiary sediments from the Japan Trench (DSDP Leg 56, Sites 434 and 436; and Leg 57, Sites 438, 439 and 440) were determined. The hydrocarbons in lipid extracts were analyzed by capillary- column gas chromatography and combined gas chromatography/ mass spectrometry. Kerogen concentrates were investigated by microscopy, and vitrinite-reflectance values were determined. Measured organic-carbon values were in the range of 0.13 to 1.00 per cent. Extract yields, however, were extremely low. Normalized to organic carbon, total extracts ranged from 4.1 to 15.7 mg/g Corg. Gas chromatography of non-aromatic hydrocarbons showed that all sediments, except one Oligocene sample, contained very immature, mainly terrigenous organic material. This was indicated by n-alkane maxima at C29 and C31 and high odd-carbon-number predominances. Unsaturated steroid hydrocarbons were found to be major cyclic compounds in lower- and middle-Miocene samples from the upper inner trench slope (Sites 438 and 439). Perylene was the dominating aromatic hydrocarbon in all but the Oligocene sample. Microscopy showed kerogens rich in terrigenous organic particles, with a major portion of recycled vitrinite. Nevertheless, almost all the liptinite particles appeared to be primary. This is a paradox, as the bulk of the samples were composed of hemipelagic mineral matter with a major siliceous biogenic (planktonic) component. A trend of reduced size and increased roundness can be seen for the vitrinite/ inertinite particles from west to east (from upper inner trench slope to outer trench slope). All sediments but one are relatively immature, with mean huminite-reflectance values (Ro)in the range of 0.30 to 0.45 per cent. The oldest and deepest sediment investigated, an Oligocene sandstone from Site 439, yielded a mean vitrinitereflectance value of 0.74 per cent and a mature n-alkane distribution. This sample may indicate a geothermal event in late Oligocene time. It failed to affect the overlying lower Miocene and may have been caused by an intrusion. Boulders of acidic igneous rocks in the Oligocene can be interpreted as witnesses of nearby volcanic activity accompanied by intrusions.
Supplement to: Rullkötter, J et al. (1980): Organic geochemistry of sediments cored during Deep Sea Drilling Project Legs 56 and 57, Japan Trench: Organic petrography and extractable hydrocarbons. In: Scientific Party, Initial Reports of the Deep Sea Drilling Project, 56/57 (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 56-57, 1291-1304, https://doi.org/10.2973/dsdp.proc.5657.162.1980